Zakat and Community Empowerment: Synergizing Public Governance to Enhance Social Welfare - Shodiq, Muhammad Fajrus (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This study explores the strategic integration of zakat within the framework of public administration to enhance community empowerment and improve social welfare in Indonesia. Employing a descriptive qualitative methodology, the research analyzes scholarly literature and policy documents, including national regulations and institutional practices related to zakat governance. The findings highlight that when managed transparently and aligned with good governance principles, zakat functions as more than a religious obligation—it serves as a potent tool for social justice, economic empowerment, and poverty alleviation. Institutional actors such as BAZNAS and LAZISMU exemplify how zakat management can incorporate participatory, accountable, and effective administrative practices to support national welfare agendas. The discussion underscores the importance of policy integration, supportive regulatory environments, and multi-stakeholder collaboration to amplify the impact of zakat-based programs. This synergy between zakat and public governance offers a conceptual and practical model for developing a sustainable, values-based social welfare system. The study concludes by identifying the need for further research into cross-sector collaboration models and the institutionalization of zakat within broader social policy frameworks.